2021
DOI: 10.1063/5.0058789
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate modification of electronic nonadiabaticity: H atom scattering from p(2 × 2) O on Pt(111)

Abstract: We report inelastic differential scattering experiments for energetic H and D atoms colliding at a Pt(111) surface with and without adsorbed O atoms. Dramatically, more energy loss is seen for scattering from the Pt(111) surface compared to p(2 × 2) O on Pt(111), indicating that O adsorption reduces the probability of electron–hole pair (EHP) excitation. We produced a new full-dimensional potential energy surface for H interaction with O/Pt that reproduces density functional theory energies accurately. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…A series of scattering experiments have been performed in which high-energy H atoms were shot onto fcc(111) metal surfaces. In combination with electronically nonadiabatic molecular dynamics (MD) simulations, it was demonstrated that the energy transfer from the projectile to the metallic surface is dominated by electronic excitations. When the metal surface is exchanged with a noble-gas surface, however, the excess energy is completely taken up by the lattice, and surface penetration was identified to be the first step in adsorption . Regardless of the recent advance on H atom scattering studies, the role of the surface structure has not been the subject of investigation yet.…”
Section: Introductionmentioning
confidence: 99%
“…A series of scattering experiments have been performed in which high-energy H atoms were shot onto fcc(111) metal surfaces. In combination with electronically nonadiabatic molecular dynamics (MD) simulations, it was demonstrated that the energy transfer from the projectile to the metallic surface is dominated by electronic excitations. When the metal surface is exchanged with a noble-gas surface, however, the excess energy is completely taken up by the lattice, and surface penetration was identified to be the first step in adsorption . Regardless of the recent advance on H atom scattering studies, the role of the surface structure has not been the subject of investigation yet.…”
Section: Introductionmentioning
confidence: 99%
“…While the former depends mainly on the metal at hand, the latter is affected by both the impurity and the metal. 59 We analyzed the atomic projected DOS (see Sec. III C in the supplementary material) and confirmed that Pd and Pt are, at the same time, the systems that present the largest electronic friction values and the highest DOS at the Fermi level among the transition metals.…”
Section: Hopping Of Hydrogen and Deuterium In Bulk Metals A Minimum E...mentioning
confidence: 99%
“…11 via the Fermi-Dirac factors, the latter contributes via the strength of the nonadiabatic coupling. While the former depends mainly on the metal at hand, the latter is affected by both the impurity and the metal 63 . We analyzed the atomic projected DOS (see section III C in the SI) and confirmed that Pd and Pt are, at the same time, the systems that present the largest electronic friction values and the highest DOS at the Fermi level among the transition metals.…”
Section: Hopping Of Hydrogen and Deuterium In Bulk Metals A Minimum E...mentioning
confidence: 99%